Perbandingan efektivitas teknik modifikasi dan konvensional pada operasi open pyelolithotomy batu staghorn - I Gede Hendra Sucipta; Anak Agung Gde Oka; I Gede Raka Widiana (DiscoverSys Inc., 2019)
Background: Open pyelolithotomy for staghorn stone patient management has a high stone-free rate. The disadvantages of open pyelolithotomy include aesthetics and postoperative complications, so a breakthrough to reduce these complications is needed, which can be achieved by doing modified open pyelolithotomy.Objective: To compare the modified and conventional open pyelolithotomy techniques according to the duration of operation, the volume of surgical bleeding, pain, and post-operative drop in hemoglobin (Hb).Method: A quasi-experimental study with twenty-two samples of staghorn stone patients was collected from October 2016 to October 2017. Parametric tests were used as data were normally distributed and homogeneous. The independent t-test was used to compare each measured parameter according to the type of operation. Analysis of covariance (ANCOVA) was used to control the variables of age, gender, and body mass index (BMI).Result: The modified technique had a shorter operating duration than the conventional method (p < .05). The volume of surgical bleeding in the modified technique was lower compared to the conventional technique (p < .05). Pain scores in the modified technique were lower than the conventional technique (p <Â .05). The drop in Hb levels in the modified technique was lower than the conventional technique (p < .05). Analysis using ANCOVA found that the type of operation has a direct effect on the duration of operation, volume of surgical bleeding, and post-operative pain.Conclusion: The modified open pyelolithotomy technique was more effective than the conventional open pyelolithotomy technique based on the duration of operation, the volume of surgical bleeding, and post-operative pain scale. In this study, it was found that the drop in Hb levels was not directly affected by the type of surgery.